Identification of novel small RNAs in extracellular vesicles produced by Actinobacillus pleuropneumoniae - da Silva, Giarlã Cunha; Rosa, Jéssica Nogueira; Fontes, Patrícia Pereira; de Castro, Alex Gazolla; Barbosa, Éverton De Almeida Alves; Clarindo, Wellington Ronildo; Mantovani, Hilário Cuquetto; Li, Yanwen; Bossé, Janine Thérèse; Langford, Paul Richard; Bazzolli, Denise Mara Soares (Frontiers in Microbiology, 2023)
Extracellular vesicle (EV) production by bacteria is an important mechanism for microbial communication and host-pathogen interaction. EVs of some bacterial species have been reported to contain nucleic acids. However, the role of small RNAs (sRNAs) packaged in EVs is poorly understood. Here, we report on the RNA cargo of EVs produced by the pig pathogen Actinobacillus pleuropneumoniae, the causal agent of porcine pleuropneumonia, a disease which causes substantial economic losses to the swine industry worldwide. The EVs produced by aerobically and anaerobically grown bacteria were only slightly different in size and distribution. Total cell and outer membrane protein profiles and lipid composition of A. pleuropneumoniae whole cell extracts and EVs were similar, although EVs contained rough lipopolysaccharide compared to the smooth form in whole cells.Approximately 50% of Galleria mellonella larvae died after the injection of EVs. RNAseq, RT-PCR, protection from nuclease degradation, and database searching identified previously described and thirteen novel A. pleuropneumoniae sRNAs in EVs, some of which were enriched compared to whole cell content. We conclude that A. pleuropneumoniae EVs contain sRNAs, including those known to be involved in virulence, and some with homologs in other Pasteurellaceae and/or non-Pasteurellaceae. EvsRna2 Yes Yes Yes Yes Yes EvsRna3 No No NA** No No EvsRna4 Yes Yes Yes Yes Yes EvsRna5 No No NA*** No No